SIMULTANEOUS ELECTIONS AND ITS FEASIBILITY: Examining the Need for Simultaneous Elections and Potential Measures (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Democracy is the most wonderful process of people’s participation in deliberation as regards the formation of government. However this wonderful process has been not been subjected to experimentations in last many years and thus it has become a subject of wide scepticism. Today elections have become fossils of democracy. There is growing chorus for holding simultaneous elections on backdrop of failing electoral system. However such a phenomenal change in structural framework, which has its own ramifications on the Basic Structure of great edifice, the Constitution of India, can’t be done without due reflexion and considered reasons. The paper herein therefore tries to analyse the reasons for the need of simultaneous polls and measures that can be undertaken in adopting the said process.